Predictors of clinical outcomes in ischemic stroke patients with infectious complications - Juniarto Mende; Graciano A. Maturbongs; Yohana K.A. Mbulang (Jurnal Biologi Papua, 2026)
Infection in stroke patients is a significant health problem that is associated with poor prognosis and increased treatment costs. This infection can intensify immune system dysregulation, worsen the risk of cognitive decline, and increase mortality and neurological disability. This study aimed to evaluate predictors influencing clinical outcomes in ischemic stroke patients with infectious complications. The study used a cross-sectional design. Retrospective data were collected from medical records at Jayapura Regional Hospital for the period from January 1, 2023, to May 31, 2025. The study subjects were all patients with ischemic stroke who received antibiotics. Clinical outcomes were evaluated based on clinical improvement, defined by vital signs within the normal range, symptom improvement within three to five days after antibiotic administration, and improvement in laboratory values to within the normal range. A total of 50 patients were included after meeting the study inclusion criteria. The results showed significant relationships between risk factors such as hypertension, kidney failure, respiratory tract infection (pneumonia), and rational antibiotic use, with p-values of 0.007, 0.016, 0.023, and 0.007, respectively, and the clinical outcomes of ischemic stroke patients with infectious complications. Multivariate analysis showed that the factors influencing clinical outcomes were hypertension (OR= 7.292; 95% CI 1.510–35.202; p= 0.013), kidney failure (OR= 1.565; 95% CI 0.027–0.810; p= 0.028), respiratory tract infection (pneumonia) (OR= 5.760; 95% CI 1.147–28.920; p= 0.033), and rational antibiotic use (OR= 7.292; 95% CI 1.510–35.202; p= 0.013). Monitoring risk factors in post-infectious ischemic stroke patients is therefore essential. Pharmacists can play an important role in monitoring patients’ clinical conditions to prevent post-stroke complications by paying close attention to patient risk factors.